Pharmaceutical Care Workload and Human Resources Requirements at MOH Hospitals during Nine years Mass Gathering Hajj (2006-2014) in Al-Madina Region, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the pharmaceutical care workload analysis and workforce requirements at Ministry of Health Hospitals during mass gathering Hajj nine years (2006-2014) in Al-Madina Region, Saudi Arabia. Methods: It is a retrospective of nine years (2006-2014) of hospital pharmacies workload during mass gathering Hajj period. The duration of workload collection was 15-30 days each year. The pharmacists provide pharmaceutical to all patients either Pilgrim or not Pilgrim at Madina region. The workforce requirements calculated based on MOH workforce standards per bed and the workload drives as central pharmacy services, patient specific pharmacy activities, and general administration specific pharmacy activities. Results: The total number of Pilgrims (1,952,817-3,161,573) with average (2,445,208). The total number of prescriptions was (22,278-133,107) with an average of (78,955). It represented (1.07-5.02%) with an average (3.11%) of all pilgrims. The average number of pharmacist needed (6.41 FTE) for inpatient services per hospital, (22.96 FTE) for Emergency services per hospital, and (109.02 FTE) for Ambulatory care services per hospital. The average number of pharmacist calculated per hospital was (29.5 FTE), while the mean number pharmacist needed to base on workload for all services was (24.4 FTE) per hospital. There were not any central pharmacy activities, and clinical pharmacy services or administrative pharmacy activities. Conclusion: The pharmacy workload analysis reflects the real demand of pharmacist. Despite clinical pharmacy, activities missed with emphasis on inpatient clinical pharmacy programs; there is acceptable of number of pharmacists compared to MOH standards during mass gathering Hajj period in Al-Madina Region in Saudi Arabia.
Keywords: Pharmaceutical Care; Workload; Workforces; Mass Gathering; Hajj; Al-Madina; Ministry Of Health; Saudi Arabia